2008
DOI: 10.1088/0953-8984/20/6/064227
|View full text |Cite
|
Sign up to set email alerts
|

Materials design and development of functional materials for industry

Abstract: It is now well recognized that we are witnessing a golden age of innovation with novel materials, with discoveries that are important for both basic science and industry. With the development of theory along with computing power, quantum materials design-the synthesis of materials with the desired properties in a controlled way via materials engineering on the atomic scale-is becoming a major component of materials research. Computational prediction based on first-principles calculations has helped to find an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 40 publications
0
23
1
Order By: Relevance
“…[ 56 ] And Asahi et al reported a liquid quench approach followed by SPS to prepare HH compounds with improved homogeneity and TE properties. [ 57 ] Birkel et al used microwave heating to prepare TiNiSn and TiCoSb, reducing the reaction time signifi cantly from more than a week to one minute. [ 58 ] A combined ball milling and hot pressing approach was adopted to obtain nanostructured HH alloys by Yan et al [ 59 ] Nevertheless, impurity phase is still an obstacle for these methods to rapidly obtain high quality products.…”
Section: Rapid Fabrication and Atomic Disordersmentioning
confidence: 99%
“…[ 56 ] And Asahi et al reported a liquid quench approach followed by SPS to prepare HH compounds with improved homogeneity and TE properties. [ 57 ] Birkel et al used microwave heating to prepare TiNiSn and TiCoSb, reducing the reaction time signifi cantly from more than a week to one minute. [ 58 ] A combined ball milling and hot pressing approach was adopted to obtain nanostructured HH alloys by Yan et al [ 59 ] Nevertheless, impurity phase is still an obstacle for these methods to rapidly obtain high quality products.…”
Section: Rapid Fabrication and Atomic Disordersmentioning
confidence: 99%
“…Despite the wealth of literature on N-doped TiO 2 , 6 there is little consensus on whether this leads to an overall improvement in sunlight driven photocatalysis. [7][8][9][10][11][12] Cationic dopants with a higher oxidation state than Ti 4+ do not reduce the visible light response of anatase TiO 2 . Instead they act as electron donors, injecting electrons into the conduction band, and can transform anatase into a transparent conducting oxide (TCO).…”
Section: Introductionmentioning
confidence: 99%
“…The prolific work reported by Asahi et al [1] in which nitrogen doping was identified as a promising approach for an effective bandgap narrowing of TiO 2 has spawned active discussion and controversy in the last decade [2][3][4][5][6]. For the most part, the discussion around nitrogen-doped TiO 2 materials (henceforth N-TiO 2 ) has been focused on their visible light activity and its origins.…”
Section: Introductionmentioning
confidence: 99%